2017
DOI: 10.1136/jmedgenet-2017-104555
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the first dominant mutation of LAMA5 gene causing a complex multisystem syndrome due to dysfunction of the extracellular matrix

Abstract: This is the first report of a disease phenotype associated with mutation in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…In the literature, LAMA5 has been observed to cause complex multisystem syndromes (skin anomalies, muscle weakness, joint and internal organ ligament laxity, etc.) due to dysfunction of the extracellular matrix (Sampaolo et al, ). Such phenotypes were present in members of three generations in the paper.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, LAMA5 has been observed to cause complex multisystem syndromes (skin anomalies, muscle weakness, joint and internal organ ligament laxity, etc.) due to dysfunction of the extracellular matrix (Sampaolo et al, ). Such phenotypes were present in members of three generations in the paper.…”
Section: Discussionmentioning
confidence: 99%
“…The role of LN-α5 in promoting dermal papilla development and its function during early hair morphogenesis had been reported in mouse [14]. In addition, Simone and colleagues demonstrated the disease phenotype associated with LN-α5 mutation in humans including skin anomalies, impaired scarring, night blindness, muscle weakness, osteoarthritis, joint and internal organs ligaments laxity, malabsorption syndrome and hypothyroidism [15]. Thus, the qualitative and quantitative expressions of LN-α5 were different during the development stage as the regulatory molecules.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 We recently described a complex multisystem syndrome caused by an autosomal-dominant LAMA5 mutation in the second and third generations of an Italian family. 24 In this family, followed-up for 20 years, autosomal-dominant mild myopia was also observed as an independent trait. Clinical and genetic investigations on myopia, extended also to the fourth generation of the family, demonstrated that this trait was associated to a novel dominant missense variant c.1147A > G p.(Lys383Glu), in the prolyl 4-hydroxylase, alpha 2 (P4HA2) gene.…”
mentioning
confidence: 67%
“…Five subjects (II‐10, III‐7, III‐16, III‐18 and IV‐12) had uncorrected visual acuity 20/20 with emmetropia in both eyes, 6 patients (II‐4, II‐7, II‐9, III‐14, III‐17 and III‐20) had mild‐moderate myopia with a spherical equivalent of −3.05 ± 0.6D in the right eye and −2.4 ± 1.7D in the left eye. Patient III‐20 had myopia without the multisystem syndrome . Patient II‐4 was subjected to surgical refractive correction and his actual visual acuity is 8 to 9/10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation